Farrerol Ameliorated Cisplatin-Induced Chronic Kidney Disease Through Mitophagy Induction via Nrf2/PINK1 Pathway - Ma, Ning; wei, Zhentong; Hu, Jianqiang; Gu, Wenjing; Ci, Xinxin (Frontiers in Pharmacology, 2021)
Previously, Our study has showed that farrerol can activate Nrf2 and ameliorate cisplatin-induced acute kidney injury (AKI). Mitophagy reportedly can prevent diabetic nephropathy, cisplatin-induced AKI and other related nephropathy. In this study, we evaluated the correlation between mitophagy and the protective effect of the Nrf2 activator farrerol on cisplatin-induced CKD by using C57BL/6 wild-type and Nrf2 knockout mice. We confirmed that Nrf2 and PINK1/Parkin-mediated mitophagy was significantly increased on the 3rd day of cisplatin stimulation but was reduced on the 38th day of cisplatin stimulation. Similar to previous results, farrerol activated Nrf2 on the 38th day of cisplatin administration, subsequently stimulating the Nrf2-targeted antioxidant enzymes HO-1 and NQO1. In addition, farrerol triggered PINK1/Parkin-mediated mitophagy by recruiting the receptor proteins LC3 and p62/SQSTM1, thereby eliminating damaged mitochondria. Furthermore, genetic deletion of Nrf2 reduced PINK1/Parkin-mediated mitophagy activation and led to increased renal tubular necrosis and renal fibrosis. We also found that farrerol alleviated inflammation and renal fibrosis by inhibiting p-NF-κB/NLRP3 and TGF-β/Smad signaling. These data indicated that farrerol effectively inhibited cisplatin-induced inflammation and renal fibrosis by activating Nrf2 and PINK1/Parkin-mediated mitophagy, which provides a potential novel therapeutic target for CKD.